ENGINEERING PROPERTIES OF LIGHTWEIGHT FOAMED CONCRETE STRENGTHEN WITH FIBREGLASS NETTING (Jurnal Teknologi (Sciences & Engineering), 2023)
Lightweight foamed concrete (LFC) is widely recognised as a low-density concrete with multiple applications. Yet, since its weight is approximately half that of conventional concrete, its strength should also be lower. Hence, synthetic and natural short fibres were utilised by previous researchers to enhance the performance of LFC. The use of textiles as reinforcing elements has attracted substantial attention in recent years. Consequently, the purpose of this study was to conduct an experimental investigation to determine the engineering properties of LFC reinforced with fibreglass mesh netting. In this study, LFC samples with densities of 550 kg/m3 and 1150 kg/m3 were formulated using a constant cement-to-sand ratio of 1:1.5, and a cement-to-water ratio of 0.45. The LFC specimens were jacketed with 1 layer, 2 layers and 3 layers fibreglass netting. The properties determined were compressive strength, flexural strength, split tensile strength, porosity, water absorption, UPV and drying shrinkage. Accordingly, the results showed that the incorporation of fibreglass netting in LFC helps reduce the absorption of water and the porosity of LFC for all densities. In addition to crack control, fibreglass netting also improves the drying shrinkage, flexural, compressive, tensile strengths and UPV. The optimal engineering properties were achieved with the addition of 3-layer fiberglass netting for 1150 kg/m3 density LFC.